Contingent convertible bonds in European banking system: Effects on banking performance and profitability - TSAKANIKAS, VASILEIOS (2017)
This paper aims to give insight into the concept of contingent convertible (CoCo) bonds in relation to banking performance. Specifically, we analyse the profitability of European banks the period 2013-2016 and we investigate whether the implementation of CoCo bonds in the banking environment has influenced the profitability of the European banks. Moreover, we examine which determinants and characteristics affect the propensity of CoCo bond issuance. CoCo bonds absorb losses by converting into equity or by writing-down its face value when the capital of the issuing bank falls below a certain level. They have been invented as a tool to reduce the systematic risk and the too-big-to-fail issues of banks. Regarding our profitability model, we develop two distinct static model specifications to capture any potential relationship. In general, we find that CoCo bonds affect the profitability in a negative manner due to the high-yield coupon payments. Nevertheless, by controlling for endogeneity concerns in our model, we also find that CoCo bonds provide an additional boost on the positive association of equity to the banking profitability. Besides these findings, we highlight the importance of cost efficiency and liquidity in terms of profits. In the probability analysis, we use a Logit model to examine the main determinants of CoCo bond issuance. We find that cost-efficient, large and publicly-traded banks with low capital adequacy are more likely to issue CoCos. Additionally, the quality of loan portfolio, the liquidity levels and the profitability of the banks are some other dimension that affects the probability of CoCo issuance. Furthermore, CoCo issuances are significantly encouraged under a growing economy and in a highly concentrated banking system.